Using Digital Storytelling to Reduce Demotivation during Covid-19 Pandemic: A Conceptual Study - Adara, Reza Anggriyashati; Budiman, Rido; Puspahaty, Novita; Yanti, Septia Dhama (SALEE: Study of Applied Linguistics and English Education, 2022)
It has been argued that demotivation can negatively affect learners’ interests in language learning. Thus, teaching strategies need to be performed in order to prevent or overcome demotivation. In this regard, using technology improves learners’ motivation and reduces demotivation. As a part of technology integration into language classrooms, digital storytelling can be one of the strategies taken to reduce learners’ demotivation. The present study is a conceptual study that aims to describe the potential benefits of integrating digital storytelling in EFL classrooms in trying times such as the Covid-19 pandemic. Besides discussing the merits of technology integration, especially digital storytelling in language classrooms, the present study will suggest strategies to integrate digital storytelling to increase motivation and decrease demotivation. The present study may merit educators and researchers interested in the discussions about using technology to minimize demotivation during challenging times such as the Covid-19 pandemic.